Plan de negocios para la creación de una empresa de intermediación financiera para la adquisición del soat motos en la ciudad de Manizales (2013)
The issue regarding the payment at maturity SOAT has been a common theme for the inhabitants of considering Manizales is a city where the main income of the people are between 1 and 2 legal monthly minimum wage to cover only the basic needs basket and in many cases the budget is not enough cash to pay the full value of this. Within the development of the research project will generate a business plan to facilitate the purchase of SOAT (Traffic Accidents Compulsory Insurance) and the benefits that this implies if one day SOAT as required by law, as a high percentage of motorcyclists drive their vehicles without having to update the documentation required by the Ministry of Traffic and Transportation, which in many cases can take from the immobilization of the vehicle or until quite high fines for not having the required documentation is why it is proposed to demonstrate through a market study which are the main factors why people do not acquire their time SOAT Research is expected to develop a business plan to present to the easy acquisition and SOAT purchase through a payroll deduction not significantly affect the basket of everyday due when the insurance on the other hand , operating as innovation method to potentiate selling SOAT insurance in the city of Manizales. To develop a business plan create a financial brokerage company to advise people to obtain credit by warrant for payment of SOAT and otherwise perform intermediation is to purchase the insurance directly SOAT with this new economic unity gain revenue from fees charged by the finance company and the insurance company will have a net interest income of $ 10,000 delivered SOAT